Path Analysis in PLS for Assessing the Impact of Metabolic Syndrome on Pulmonary Fibrosis in a Rat Model - Yaman, Muli; Djajalaksana, Susanthy; Putra, Ngakan Putu Parsama; Yudhanto, Hendy Setyo (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Metabolic syndrome (MetS) is characterized by obesity, dyslipidemia, hyperglycemia, and insulin resistance, which are associated with increased risk for pulmonary fibrosis. This study investigates the impact of MetS on pulmonary fibrosis in a rat model using Partial Least Squares (PLS) path analysis. Methods: Sprague Dawley rats were fed a high-fat, high-fructose diet for 37 weeks to induce MetS. Key metabolic parameters, including body weight, lipid profiles, fasting blood glucose, fibrosis markers and Aschroft scores, were assessed. PLS path analysis was conducted to explore the relationships between these variables and their influence on pulmonary fibrosis. Results: PLS path analysis identified a strong correlation between increased body weight and MetS development (path coefficient=0.977). Dyslipidemia, characterized by elevated triglycerides and reduced HDL cholesterol, was also associated with MetS. A novel association was found between glucose dysregulation and pulmonary fibrosis (R2=0.908; path coefficient=0.947), suggesting that hyperglycemia contributes to lung fibrosis. Reduced PPARγ expression was associated with insulin resistance and inflammation, implicating it in fibrotic processes. Conclusion: This study highlights the role of metabolic disturbances in promoting pulmonary fibrosis in MetS. PLS path analysis effectively identified key metabolic pathways, suggesting potential targets for therapeutic intervention to mitigate MetS effects and prevent fibrosis. Further research is warranted to explore these pathways and develop targeted therapies.